2013
DOI: 10.1111/j.1600-0587.2013.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐mediated habitat selection in an arboreal folivore

Abstract: Th e decisions that animals must make to achieve a balance between quantity and quality of resources become more diffi cult when their habitats are patchy and diff er greatly in quality across space and time. Koalas are a prime subject to study this problem because they have a specialised diet of eucalypt leaves and need to balance nutrient and water intake against toxins in the leaves, all of which can change with soil type and climate. Koalas are nocturnal and spend most of the day resting and therefore choo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 72 publications
2
50
0
Order By: Relevance
“…For koalas, tree-hugging behaviour greatly reduced predicted heat loss requirements, and water savings from this behaviour could be critical for the survival of this species during heat waves when water availability is limited [14], or under high humidity when evaporative cooling is inefficient [2]. Our results are consistent with, and may help explain, previous studies of koalas in more northern populations that found seasonal [18] and weather-dependent differences in tree use, with koalas using non-food trees more frequently during hot days [6,19]. Combined, these results emphasize the importance of behavioural thermoregulation for koalas [6] and highlight that trees (including non-food trees) that provide cool tree trunks or dense shade are an important component of habitat quality for this species.…”
Section: Discussionsupporting
confidence: 82%
“…For koalas, tree-hugging behaviour greatly reduced predicted heat loss requirements, and water savings from this behaviour could be critical for the survival of this species during heat waves when water availability is limited [14], or under high humidity when evaporative cooling is inefficient [2]. Our results are consistent with, and may help explain, previous studies of koalas in more northern populations that found seasonal [18] and weather-dependent differences in tree use, with koalas using non-food trees more frequently during hot days [6,19]. Combined, these results emphasize the importance of behavioural thermoregulation for koalas [6] and highlight that trees (including non-food trees) that provide cool tree trunks or dense shade are an important component of habitat quality for this species.…”
Section: Discussionsupporting
confidence: 82%
“…Crowther et al, 2014;Santika et al, 2014;Seabrook et al, 2014) has established that there are multiple interacting factors that will determine koalas' vulnerability to climate change. There is increasing evidence that koalas and some koala food trees will experience significant range contractions as climate change progresses (Adams-Hosking et al, 2011aSeabrook et al, 2011Seabrook et al, , 2014Lunney et al, 2014).…”
Section: Challenge 2: Adapting To Climate Changementioning
confidence: 97%
“…The quality of koala habitat and food is closely linked to the distribution of the more nutrient-rich foliage of particular eucalypt species, often occurring on the more fertile soils ). In addition, a range of non-food species will determine the suitability of habitat by providing microclimatic refuges during heatwaves Ellis et al, 2010;Crowther et al, 2014). Refugia, especially those that provided refuge during previous droughts, are particularly important to maintain koala populations in perpetuity (Adams-Hosking et al, 2011b).…”
Section: Challenge 2: Adapting To Climate Changementioning
confidence: 99%
“…It is a specialized arboreal folivore that feeds predominantly on Eucalyptus and Corymbia species. Its highly specific diet varies within regional areas due to variation in local soil characteristics, tree structure, leaf water and chemical content (Moore et al ., 2004b; Lunney et al ., ; Crowther et al ., ). Resources and habitat quality are major influences on population persistence and are particularly important for habitat specialists, such as the koala (Smith et al ., 2013b).…”
Section: Introductionmentioning
confidence: 97%